Cultivating the Values of Religious Moderation Among IAIN Palopo Students - Andi Riawarda; Naidin Syamsuddin (State Islamic Institute of Palopo, 2023)
The purpose of the study was to determine the values ​​of religious moderation among IAIN Palopo students. Religious moderation can be understood as a perspective, attitude, and behavior in the middle position without being excessive in religion, that is, not being extreme. What is meant here is no exaggeration to place an understanding at a high level of wisdom by paying attention to religious texts, state constitutions, local wisdom, and mutual consensus. This research method is descriptive qualitative research. Research that seeks to describe problem-solving based on data. This study explains that cultivating religious moderation through religious subjects aims to provide education to students about strengthening religious understanding. Some of the contributions of the house of moderation in fostering religious moderation are; first, facilitating the strengthening and socialization of moderate Islamic ideas; second, providing understanding to students as agents of change in society regarding the need for tolerance; third, managing diversity in diversity and promoting itself as a campus of